Higher thyrotropin concentration is associated with increased incidence of colorectal cancer in older men - Chan, Y.; Alfonso, Helman; Chubb, S.; Fegan, P.; Hankey, G.; Golledge, J.; Flicker, L.; Yeap, B. (Blackwell Publishing Ltd, 2016)
© 2016 John Wiley & Sons Ltd.Context: Thyroid hormones regulate cellular survival and metabolism; however, their association with cancer incidence and death has not been well explored. Objectives: Our aim was to examine the relationship between thyrotropin (TSH) and free thyroxine (FT4) with cancer incidence (all cancers, prostate, colorectal and lung cancer). Associations with cancer-related deaths were also explored. Design and setting: A prospective cohort study involving community-dwelling men aged 70-89 years. Main outcome measures: Thyroid hormones were measured in 3836 men between 2001 and 2004. Competing risks analyses were used to perform longitudinal analyses with results expressed as subhazard ratios (SHR). Outcomes were ascertained through electronic linkage until 20 June 2013. Results: Mean age was 77·0 ± 3·6 years. A total of 864 men developed cancers, and 506 experienced cancer-related deaths. A total of 340, 136 and 119 men developed prostate, colorectal and lung cancers, respectively. After adjustments, there were no associations between TSH and incidence of all cancers, prostate or lung cancer. Higher TSH was associated with increased colorectal cancer incidence (SHR = 1·19, 95% CI 1·00-1·42; P = 0·048 for every 1 SD increase in log TSH). This association was strengthened after excluding the first year of follow-up (SHR = 1·23, 95% CI 1·02-1·48, P = 0·028). FT4 was not associated with incidence of all cancers, prostate, colorectal or lung cancer. Thyroid hormones were not associated with cancer-related deaths. Conclusion: In community-dwelling older men, FT4 was not associated with cancer incidence. Higher TSH is independently associated with increased incidence of colorectal cancer. Further investigation is warranted to determine whether a causal relationship exists.